Case Report: Parkinsonism with Normal Pressure Hydrocephalus and Recurrent Seizures in an Elderly Male - Gk, Parigodson.; T, Immanuvel.; M, Aravind.; Karthickeyan, K.; Sundaram, P. Shanmuga; Dheenadhayalan, M.; Sri, M.K. Sundar (Journal of Neonatal Surgery, 2025)
This case report discusses a 64-year-old male patient with a complex medical history involving Parkinson’s disease, dementia, and normal pressure hydrocephalus (NPH), who presented with recurrent seizures and altered sensorium following a fall. The patient was also diagnosed with systemic hypertension, syncope, recurrent aspiration pneumonia, and a seizure disorder. This case emphasizes the challenges of managing multiple overlapping neurological and systemic conditions in a geriatric patient and highlights the importance of multidisciplinary care, pharmacological adjustments, and clinical pharmacist interventions in optimizing treatment outcomes.